The new Labor Procedure Law and the problematic delimitation of social security: For an all-encompassing labor justice or a specialized social security justice? - Paitán Martínez, Javier (2021)
This article analyzes the problems raised by social security conflicts, as a result of the unique protection provided by Law No. 29497, New Labor Procedural Law (hereinafter NLPT), which consolidates the competence of labor judges in matters of social security benefits, previously determined by the Organic Law of the Judiciary. Thus, the need for a review and possible reform of the NLPT arises, following a true social security justice with its own procedure, rules and principles.